2021
DOI: 10.3390/ijerph18179271
|View full text |Cite
|
Sign up to set email alerts
|

Sort and Sieve: Pre-Triage Screening of Patients with Suspected COVID-19 in the Emergency Department

Abstract: Introduction. To reduce the risk of nosocomial transmission, suspected COVID-19 patients entering the Emergency Department (ED) were assigned to a high-risk (ED) or low-risk (acute medical unit, AMU) area based on symptoms, travel and contact history. The objective of this study was to evaluate the performance of our pre-triage screening method and to analyse the characteristics of initially undetected COVID-19 patients. Methods. This was a retrospective, observational, single centre study. Patients ≥18 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Several studies revealed that the screening process for EID patients was very effective in preventing disease transmission. One of the studies indicated a pre-triage screening accuracy of 63.7% (Hensgens et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies revealed that the screening process for EID patients was very effective in preventing disease transmission. One of the studies indicated a pre-triage screening accuracy of 63.7% (Hensgens et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…On this basis, a decision is made whether to treat the patient in the hospital or at home. Hensgens suggested that ED screening protocols should include non-specific complaints, particularly in older patients, to improve early identification and proper segregation [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 , 6 Although the current literature offers different models of COVID-19 triage systems, either based on simple statistical methods or artificial intelligence-driven models, some concerns remain regarding their validity and generalisability. 7 , 8 …”
mentioning
confidence: 99%